Claude GERMAIN. The Neurolinguistic Approach (NLA) for Learning and Teaching Foreign Languages: Theory and Practice. Newcastle upon Tyne, UK: Cambridge Scholars Publishing, 2018. xi + 231pp. - Lopes Ângela Filipe (Linguarum Arena, 2019)
.